Whole-genome transposon mutagenesis to elucidate the genetic requirements for vitamin B12 biosynthesis and assimilation in mycobacteria - Mbau, Rendani Donald (Department of Clinical Laboratory Sciences, 2022)
Comparative genomic analyses have identified an altered capacity for cobalamin biosynthesis as a critical step in the evolution of the pathogenic Mycobacterium tuberculosis Complex strains from a common environmental ancestor. However, resolving the full gene complement involved in the complex, multi-step pathway for de novo cobalamin biosynthesis, assimilation, and salvage in different mycobacterial species is challenging. A genome-scale approach was adopted to yield detailed genetic maps of de novo cobalamin biosynthesis in M. smegmatis, a non-pathogenic saprophyte. To this end, a combination of whole-genome transposon (Tn) mutagenesis and next generation sequencing (TnSeq) was applied in M. smegmatis ΔmetE, a gene-deletion mutant in which the cobalamin-independent methionine synthase is inactivated, rendering the cobalamin-dependent isoform, MetH, essential for viability. Following growth of the metE mutant in rich medium, genomic DNA was extracted, amplified by PCR, and subjected to high-throughput sequencing to quantify all Tn junctions. Thereafter, the library was cultivated in defined minimal medium to enable identification of all conditionally essential genes – including those required for de novo cobalamin biosynthesis. A ∆metE library comprising 400,000 individual Tn insertion mutants (cfu/ml) was generated. Of the predicted 6,716 genes in the M. smegmatis genome, 213 genes were identified as essential for growth on rich agar while 356, 301, and 337 genes were identified as essential in unsupplemented, cyanocobalamin (CNCbl; vitamin B12)-supplemented and cobalt-supplemented Sauton's minimal medium, respectively. A total of 424 genes were identified as essential across all conditions tested with only 10, 13 and 24 genes (ES plus GD) uniquely required for growth in unsupplemented, CNCbl-supplemented and cobalt supplemented Sauton's minimal medium, respectively. On average, predicted cobalamin pathway genes were underrepresented in number of Tn insertions and read counts, indicating the likely essentiality of these genes during growth of the metE mutant in minimal medium. Notably, elucidation of cobalamin biosynthetic and assimilatory genes required the analysis of libraries exposed to CNCbl-unsupplemented minimal media for extended durations, probably reflecting the need to exhaust the organism's capacity for co-factor storage and recycling. Utilizing targeted silencing of individual genes by CRISPR interference, candidate cobalamin biosynthesis genes were validated, providing functional evidence of their essentiality for metE survival in minimal medium, in turn supporting the validity of the cobalamin biosynthetic pathway constructed from the TnSeq results. In addition, the results add further evidence in support of the functionality of the cobalamin riboswitch upstream of metE. This is an important observation as it suggests the potential to apply an analogous approach in M. tuberculosis, a major human pathogen whose ability to synthesize cobalamins remains unresolved. Moreover, elucidating the genetic requirements for optimal growth under specific conditions can inform our basic understanding of mycobacterial physiology and pathogenicity, identifying potential vulnerabilities for novel anti-tuberculosis therapeutics.